Crystal transition behavior of odd–odd nylon 11, 11 under annealing and stretching. Issue 12 (29th December 2013) - Liu, Shaobing; Fu, Peng; Liu, Minying; Li, Zhaopeng; Lv, Zhengya; Zhao, Qingxiang
<x xml:space="preserve">Abstract</x> Nylon 11, 11 is a new odd–odd polyamide with multiple crystalline structures. The wide‐angle X‐ray scattering indicated that the structure of quenched sample was not amorphous but a γ‐form crystal with a relatively low crystallinity. The α‐form and the γ‐form crystal of nylon 11, 11 could be obtained by annealing the quenched samples at high and low temperature, respectively. No crystal transition happened for the α‐form sample when annealed at any temperature before melting. However, the γ‐form would quickly transform into the α‐form when annealed above 145°C. Under the stretching conditions, the α‐form rapidly transformed into the γ‐form at low temperature, while the γ‐form changed into the α‐form only at high temperature. These results indicated that the stretching inducement was beneficial to produce the γ‐form, and the thermal inducement was favorable to forming the α‐form. POLYM. ENG. SCI., 54:2785–2790, 2014. © 2013 Society of Plastics Engineers